Organizational Challenges of Women Career Development: A Case Study of Banking Sector - Owunna, Royal; Aziz, Faiq; Musa, Siti Nur Syuhada; Ajobi, Alice Omoefe (HRMARS, 2024)
This study investigates the influence of organizational challenges on women's career development in the banking industry, The importance of this research lies in the influence of growth opportunities as a key factor in enhancing career development and performance. Using a qualitative approach and a case study design, data were collected through in-depth interviews with 15 employees, participant observation, and document analysis. The results show that growth opportunities significantly improve career development and performance by increasing employee motivation and commitment. On the other hand, gender stereotypes has negatively effect with career development and performance, highlighting the need for fairness and implementing work equity management practices that support innovation and reinforce positive career development and organizational performance. This research provides valuable insights for leaders of the banking industry on the importance of choosing appropriate growth opportunities for their employees and emphasizes fair organizational culture in achieving business success. The study recommended that to minimize the limitation of self-reporting data, further study is required to adopt a quantitative research technique.